PERKEMBANGAN PERBANKAN SYARIAH DI NEGARA ISLAM: perbankan syariah, - Riki Saputra; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research examines the development of sharia banking in Indonesia, which has experienced significant growth in recent years. With the largest Muslim population in the world, sharia banking offers products and services according to Islamic principles, attracting people's interest in transactions without usury. Supporting factors for this growth include expanding office networks, ease of access, educational programs, and improving service quality that is comparable to conventional banks. However, challenges such as providing quality human resources, sustainable product innovation, and sustainability of socialization programs still have to be faced. In addition, changes in supervision of the banking sector from Bank Indonesia to the Financial Services Authority (OJK) require the adaptation of new regulations. With the support of good regulations and continuous innovation, sharia banking is expected to strengthen its position in the Indonesian financial system and increase financial inclusion among Muslim communities.